2022
DOI: 10.5751/es-13570-270342
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of the COVID-19 pandemic on the use of wildlife as food among indigenous people and local communities in South America

Abstract: The COVID-19 pandemic has had a range of effects on the environment and particularly on wildlife, through diverse and sometimes contradictory impact pathways. In this study, based on data collected among indigenous people and local communities from South America (Colombia, Ecuador, Guyana, and Peru), we investigated changes in the use of wildlife resources for food during the first months of the COVID-19 pandemic. Our study generated unique data collected from 756 households in 60 communities and nine sites. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Data collected from Indigenous communities and local populations in South America, specifically Colombia, Ecuador, Guyana, and Peru, demonstrated that wildlife consumption increased as a short-term response to food insecurity during the pandemic. However, the rise in wild meat consumption was hindered by high prices and limited availability due to unsuccessful hunts [38]. These findings highlight the diverse coping strategies employed by individuals and communities to address food access challenges during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected from Indigenous communities and local populations in South America, specifically Colombia, Ecuador, Guyana, and Peru, demonstrated that wildlife consumption increased as a short-term response to food insecurity during the pandemic. However, the rise in wild meat consumption was hindered by high prices and limited availability due to unsuccessful hunts [38]. These findings highlight the diverse coping strategies employed by individuals and communities to address food access challenges during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, rural families, facing restricted livelihood options and increased urban-rural migration during the pandemic, may have increasingly relied on wild meat as a crucial source of food and income. Nonetheless, McNamara et al's hypotheses are yet to be tested quantitatively: previous attempts to assess the impacts of the COVID-19 shock on wild meat extraction and use mostly used qualitative interviews collected retrospectively and often focusing on single species (Enns et al, 2023;Mendiratta et al, 2022;Vliet et al, 2022;Kamogne Tagne et al, 2022;Briceño-Méndez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The hunting of wild animals for food (i.e., wild meat) is one of the biggest threats to biodiversity globally (Abernethy et al, 2013;Schulze et al, 2018) while also providing food and income to many rural communities across the tropics and subtropics (Coad et al, 2019). Wild meat is an easily accessible resource with relatively low entry costs, compared to other livelihood activities (Schulte-Herbrüggen et al, 2013) and, therefore, can provide an important safety net for rural communities during socio-economic crises, civil conflicts, or other shocks characterized by reductions in livelihood opportunities and market access (UNDP, 2023). The economic importance of wild meat to rural communities is well known (Nielsen et al, 2017;Schulte-Herbrüggen et al, 2013), but there is limited quantitative evidence of its use during shocks, potentially because of their unpredictability and hence the lack of comparable data before, during, and afterward.…”
Section: Introductionmentioning
confidence: 99%